2010
DOI: 10.1007/s11104-010-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential soil carbon sequestration in a semiarid Mediterranean agroecosystem under climate change: Quantifying management and climate effects

Abstract: Climate change is projected to significantly impact vegetation and soils of managed ecosystems. In this study we used the ecosystem Century model together with climatic outputs from different atmosphereocean general circulation models (AOGCM) to study the effects of climate change and management on soil organic carbon (SOC) dynamics in semiarid Mediterranean conditions and to identify which management practices have the greatest potential to increase SOC in these areas. Five climate scenarios and seven managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 43 publications
1
27
1
Order By: Relevance
“…Soil management techniques such as no-till systems may result in lower CO 2 emissions from and greater C sequestration in the soil as compared to management systems based on intensive tillage (Figure 3) [16][17][18][19][20], although some recent studies have indicated that no-till systems may simply result in higher C accumulations in the upper 15-20 cm of the soil with no increase in C when the entire soil profile is considered [21][22][23]. Other management changes such as using cover crops, crop rotations instead of monocropping, and reducing or eliminating fallow periods can lead to C sequestration in soil [16,24] as can returning land from agricultural use to native forest or grassland [25,26]. Sequestration of C tends to be rapid initially with declining rates over time ( Figure 3) [26][27][28].…”
Section: Soils As a Part Of The Global C And N Cyclesmentioning
confidence: 99%
“…Soil management techniques such as no-till systems may result in lower CO 2 emissions from and greater C sequestration in the soil as compared to management systems based on intensive tillage (Figure 3) [16][17][18][19][20], although some recent studies have indicated that no-till systems may simply result in higher C accumulations in the upper 15-20 cm of the soil with no increase in C when the entire soil profile is considered [21][22][23]. Other management changes such as using cover crops, crop rotations instead of monocropping, and reducing or eliminating fallow periods can lead to C sequestration in soil [16,24] as can returning land from agricultural use to native forest or grassland [25,26]. Sequestration of C tends to be rapid initially with declining rates over time ( Figure 3) [26][27][28].…”
Section: Soils As a Part Of The Global C And N Cyclesmentioning
confidence: 99%
“…For instance, soil C losses associated to the implementation of irrigation have been reported in other semi-arid areas [52]. Modeling scenarios also point out the possibility of C losses upon irrigation adoption in the long term [53,54]. To date, the consequences of introducing irrigation on SQ indicators in the region and an overall SQ assessment under irrigation have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Lal (2004) and Gottschalk et al (2012) reported higher latitude regions undergoing overall losses and tropical regions undergoing overall gains. At the country or regional level, SOC change under climate change has been spatially simulated in a number of recent studies, ranging from 250 m to over 50 km resolution, including in North America Follett et al, 2012;Dib et al, 2014;Zhong and Xu, 2014;Byrd et al, 2015;Orem et al, 2015), in Asia (Hashimoto et al, 2012;Zhao et al, 2013Zhao et al, , 2015, and in Europe and the Mediterranean region (Smith et al, 2005(Smith et al, , 2006Álvaro-Fuentes and Paustian, 2011;Álvaro-Fuentes et al, 2012).…”
mentioning
confidence: 99%